Malandros sem carnavais, carnavais sem heróis : juventude, geração e sociabilidade entre jovens ligados ao Rap e ao Rock nas cidades de São Carlos, São José do Rio Preto e Ribeirão Preto - Santos, José Ricardo Marques dos (2006)
The objective of this study is to understand the construction of sociability among young groups connected with Rap and Rock in the averages cities of São Carlos, São José do Rio Preto and Ribeirão Preto. The research approaches the manner how the idea of youth is constructed from the music and the space indicating how the plurality of musical styles present on these cities make possible a logic of identification and a manner of local sociability that is realized by the short circuits.